The Effect of Physical Activities and Smoking Habits toward Incidence of Stroke on Patients in Santa Elisabeth Hospital - Renova Suryani Panjaitan; Fazidah Aguslina Siregar; Albiner Siagian (Britain International for Academic Research (BIAR) Publisher, 2020)
Stroke is an important health problem in the world because stroke shows increased pain. In Indonesia, there are 500,000 people who experience strokes each year among 125,000 people die and others experience mild and severe disability. The purpose of this study is to analyze the effect of physical activities and smoking habits toward incidence of stroke on inpatients at Santa Elisabeth Hospital, Medan. This research is an observational analytic with a case control study design. Subjects consisted of cases and controls with a ratio of 1: 1 totaling 106 people namely 53 cases and 53 controls. Data collection uses interviews and questionnaires. Data analysis using simple logistic regression test. Simple logistic regression test results found that there is a significant influence between physical activity (p = 0.014; OR = 2.828, 95% CI 1,220-6,553) and smoking habits (p = 0.001; OR = 3,720, 95% CI 1,668-8,297) on the incidence stroke. It is recommended to do physical activity with adequate body movements and exercise and stop smoking.